The Mediating Role of Mother-Child Relationship and The Relationship Between Mother Phubbing and Children’s Mobile Phone Addiction in Kuala Lumpur - Mohammad Hussin, Mashitah; Che Tak, Khairudin; Motevalli, Saeid (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to explore the mediating role of the mother-child relationship in the relationship between mother phubbing and children's mobile phone addiction in Kuala Lumpur, Malaysia. Methods and Materials: A quantitative research design was utilized, involving 214 adolescents aged 13-17 in Kuala Lumpur. Data was collected using the Mother Phubbing Scale, Parent-Child Relationship Survey, and Smartphone Addiction Scale - Short Version. The mediating effects were analyzed using the Process Macro by Hayes, focusing on the relationship between mother phubbing, the mother-child relationship, and children’s mobile phone addiction. Findings: The results revealed a significant positive correlation between mother phubbing and children’s mobile phone addiction. Additionally, a significant negative correlation was found between mother phubbing and the mother-child relationship. The mother-child relationship was negatively associated with children’s mobile phone addiction. The mother-child relationship partially mediated the relationship between mother phubbing and children’s mobile phone addiction. Conclusion: This study underscores the impact of mother phubbing on children’s mobile phone addiction, mediated by the mother-child relationship. These findings highlight the need for targeted interventions focusing on enhancing parent-child relationships to mitigate mobile phone addiction in children.